Effects of Coenzyme Q10 Supplementation on Anthropometric Indices in Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Ghavami, Abed (Int J Prev Med, 2020)
BACKGROUND: Obesity is related to increase in the incidence of morbidity and mortality. Previous studies have led to conflicting results regarding the effect of coenzyme Q10 (CoQ10) supplementation on anthropometric indices. This study aimed to evaluate the efficacy of CoQ10 supplementation on body weight, body mass index (BMI), and waist circumference (WC) through a systematic review and meta-analysis of randomized controlled trials (RCTs). METHODS: PubMed, Scopus, Web of Science, and Cochrane Library as well as the reference lists of the identified relevant RCTs were searched up to March 2019, and weighted mean differences (WMDs) were pooled by using the random-effects model. RESULTS: Twenty RCTs (976 participants) were eligible to be included in the systematic review. The meta-analysis revealed that CoQ10 supplementation had no effect on body weight (WMD = −0.04 kg; 95% confidence interval [CI]: −1.96, 1.6; I(2) = 0.0%), BMI (WMD = −0.06 kg/m(2); 95% CI: −0.54, 0.42; I(2) = 0.0%), and WC (WMD = 0.79 cm; 95% CI: −2.83, 0.04; I(2) = 0.0%). CONCLUSIONS: CoQ10 supplementation might not improve anthropometric indices. Future well-designed trials are still needed to confirm these results.